2020
DOI: 10.3389/fphys.2020.00115
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome Analysis: Various Reasons of Adverse Pregnancy Outcomes Caused by Acute Toxoplasma gondii Infection

Abstract: Background: Toxoplasma gondii (T. gondii) is an obligate intracellular parasite, which can affect the pregnancy outcomes in infected females by damaging the uterus, and the intrauterine environment as well as and the hypothalamus resulting in hormonal imbalance. However, the molecular mechanisms underlying the parasite-induced poor pregnancy outcomes and the key genes regulating these mechanisms remain unclear. Therefore, this study aimed to analyze the gene expression in the mouse's uterus following experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Nonetheless, H-subcluster-specific KEGG pathways related to immune responses against T. gondii infection were still found, especially in subcluster H2. As previously reported [ 30 , 55 , 56 ], cytokine–cytokine receptor interaction (ssc04060) was found to be involved in immunomodulation of the host during acute and chronic T. gondii infection in the current study. A total of 52 genes of the pathway involving chemokines including CC and CXC subfamilies, class I helical cytokines, class II helical IL10/28-like cytokines, IL1-like cytokines, IL17-like cytokines, TNF family, and TGF-β family were potentially targeted by 31 miRNAs in subcluster H2 (Additional file 17 : Table S16).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nonetheless, H-subcluster-specific KEGG pathways related to immune responses against T. gondii infection were still found, especially in subcluster H2. As previously reported [ 30 , 55 , 56 ], cytokine–cytokine receptor interaction (ssc04060) was found to be involved in immunomodulation of the host during acute and chronic T. gondii infection in the current study. A total of 52 genes of the pathway involving chemokines including CC and CXC subfamilies, class I helical cytokines, class II helical IL10/28-like cytokines, IL1-like cytokines, IL17-like cytokines, TNF family, and TGF-β family were potentially targeted by 31 miRNAs in subcluster H2 (Additional file 17 : Table S16).…”
Section: Discussionsupporting
confidence: 82%
“…This indicates that the interactions amongst cytokines play a crucial role in the balance of the immune microenvironment during the different infection stages, such as preventing excessive immunity in acute infection and maintaining the level of inflammation to control the reactivation of T. gondii in chronic infection. In addition, several previous researchers found that the cytokine–cytokine receptor interaction pathway was also influenced by different T. gondii strains during challenge in various infection models including cat, mouse, and human cells [ 30 , 55 , 56 ], suggesting a common feature wherein interactions between cytokines and cytokine receptors have extremely important roles in the host immune responses against T. gondii , and are not strictly host-specific or strain-specific. Nonetheless, our analysis revealed that miRNAs in subcluster H2 involved in the cytokine–cytokine receptor interaction pathway may be the important immunomodulatory molecules of the host during T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%
“…Data supporting this view are emerging from various "-omics"-based profiling of the brains of mice infected by T. gondii (Jia et al, 2013;Tanaka et al, 2013;Pittman et al, 2014;Zhou et al, 2015;Hu et al, 2018;Garfoot et al, 2019a;Ma et al, 2019). The magnitude of this challenge has increased the interest in understanding how T. gondii infection affects murine host at the transcriptional level in various tissues other than the brain, including the liver (He et al, 2016a), spleen (He et al, 2016b,c), peripheral lymphocytes (Jia et al, 2013), and the uterus (Zhou et al, 2020). Increased understanding of the brain transcriptomic signature associated with T. gondii infection can provide new testable hypotheses that may ultimately facilitate the development of new treatment interventions to control cerebral toxoplasmosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, using the PubMed database [ 69 ], we compiled all the transcriptomes (that we could find) of hypertensive versus normotensive animals, as presented in Table 4 . The total number of DEGs was 4216 in 14 tissues of four animal species, as cited in the rightmost column of Table 4 [ 7 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parents of half of the hypertensive patients had hypertension, but all the known (>60) hypertension-related whole-genome human loci explained only 3% of this heritability of hypertension [ 25 ]. Maybe this is why mainstream transcriptome-profiling studies on hypertensive versus normotensive patients [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and animals [ 7 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] are focused on the differentially expressed genes (DEGs) that are specific to gender, age, and the stage of hypertension development. This is needed in predictive preventive personalized participatory (4P) medicine [ 58 ] to estimate where, how, why, and when hypertension might occur in a given patient depending on his/her genetic background.…”
Section: Introductionmentioning
confidence: 99%